PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION BERBANTUKAN LKS TERHADAP HASIL BELAJAR IPA FISIKA SISWA KELAS VII SMP N 8 PADANG - Ade Mayasari (Universitas Negeri Padang, 2013)
The Physics learning outcomes of students in Junior High School still has not optimal. This condition is caused by guidance and attention from teacher not optimal. Cooperative learning model type Group Investigation can improve the interaction between students and teacher. The earning process can be supplemented by worksheet for investigation. Therefore, the aim of this research to know the effect of Cooperative Learning model type Group Investigation with worksheet on Physics learning outcomes students VII Grade Junior High School. Population of quasi experiment research is student VII Grade in SMPN 8 Padang which registered in the academic year 2012/2013. The design of this research is Randomized Control Group Only Design. Sampling techniques that used is Cluster Random Sampling. Data were obtained through a written test for the cognitive, observation for affective domain, the observation group work for psychomotor domains and analyzed by testing the equality of two on average. The research shows there is an influence of Cooperative learning model type Group Investigation which supplemented by worksheet investigation towards learning outcome of students of Seventh Grade at SMPN 8 Padang in significant level 0.05. Keywords – Cooperative Learning, Group Investigation, Worksheet